Job competence gap of quantity surveying graduates of higher vocational colleges with a high dimensional measurement error model - Dongmei Huangfu; Yun Fah Chang (PLoS ONE, 2026)
The primary aim of this study is to measure the competency gaps between industry expectations and current competencies of recent Chinese quantity surveying graduates from higher vocational colleges, using self-reported data. An innovative measure with a high-dimensional measurement error model was utilized to evaluate competency gaps. We used a quantitative technique with purposive sampling to collect data via a questionnaire survey of quantity surveying graduates with a higher vocational diploma who had worked in China for no more than three years. The findings indicate a competency gap in job matching between quantity surveying higher vocational college graduates’ performance and industry expectations. The personality competency gap is medium, whereas the knowledge, skills, and ethical gaps are minimal. The top three gaps are in business administration, personal image, and innovative insight. The study’s findings highlight the need for training programs focused on management and personality development for quantity surveying higher vocational college graduates. They also emphasize the importance of quantity surveying professionals acquiring interdisciplinary skills through educational programs that combine management with personality attributes such as personal image and innovative insight.